The Clinical Integrative Puzzle for Teaching and Assessing Clinical Reasoning: Preliminary Feasibility, Reliability, and Validity Evidence. (1st April 2015) - Capaldi, Vincent F.; Durning, Steven J.; Pangaro, Louis N.; Ber, Rosalie
ABSTRACT: Background: Expertise in clinical reasoning is essential for high-quality patient care. The Clinical Integrative Puzzle (CIP) is a novel assessment method for clinical reasoning. The purpose of our study was to further describe the CIP, providing feasibility, reliability, and validity evidence to support this tool for teaching and evaluating clinical reasoning. Methods: We conducted a prospective, randomized crossover trial assessing the CIP in second-year medical students from a single institution. Feasibility was estimated through the time taken to complete a CIP during a CIP session and through comments from faculty developers. Reliability was addressed through calculating odd–even item reliability (split-half procedure) for grid questions within each CIP. Evidence for content, concurrent, and predictive validity was also measured. Results: 36 students participated in the study. Data suggested successful randomization of participants and nonparticipants. The CIP was found to have high feasibility, acceptable reliability (0.43–0.73 with a mean of 0.60) with a short time for CIP completion. Spearman–Brown correction estimated a reliability of 0.75 with completing two grids (estimated time of 50 minutes) and 0.82 for three grids (estimated time of 75 minutes). Validity evidence was modest; the CIP is consistent with clinical reasoning literature and the CIP modestly correlated with small group performance ( r = 0.3, p < 0.05). Conclusions: Assessing clinical reasoning in medical students is challenging. Our data provide good feasibility and reliability evidence for the use of CIPs; validity data was less robust.